Integrasi Nilai Ekoteologi untuk Menumbuhkan Kesadaran Life on Land dalam Pembelajaran IPAS di MI Darul Ulum 02 - Wafiq Azizah; Eva Luthfi Fakhru Ahsani (Alma Ata University Press, 2026)
This study aims to describe the integration of ecotheological values in Natural and Social Science (IPAS) learning to foster Life on Land awareness among fifth-grade students at MI Darul Ulum 02 Kudus. The research was motivated by the low ecological awareness of students, particularly in waste sorting and plant care within the school environment. Using a descriptive qualitative approach through observation, interviews, and questionnaires, the study implemented a Project-Based Learning (PjBL) model integrated with ecotheological values through two main projects: a demonstration of organicâ€“inorganic waste sorting and the planting of ornamental plants. The results show that ecotheological indicators were achieved with high percentages, including awareness of God’s creation (94%), ecological empathy (91%), moral and ecological ethics (87%), responsibility toward nature (81%), project collaboration (81%), spiritual ecological awareness (79%), and value reflection (72%). Life on Land indicators also demonstrated strong achievement, such as knowledge of biodiversity (81%), understanding of environmental damage (74%), environmental conservation actions (76%), and awareness of human roles (85%). Students’ responses were highly positive, with 86% in the IPAS learning aspect, 88% in the ecotheology values aspect, 87% in the life-on-land awareness aspect, and 86% in the students’ attitudes and behaviors aspect. This indicates that learners’ responses to the learning implementation were very positive.